Study of the Completion of Follow-up After Helicobacter pylori Eradication Therapy - Yusaku Kajihara; Tadashi Shimoyama (The Indonesian Journal of Gastroenterology, Hepatology and Digestive Endoscopy, 2020)
Background: Because no therapeutic regimens have an eradication rate of 100%, post-treatment evaluation is necessary to ensure that adequate eradication therapy for Helicobacter pylori has been provided. The fact that not all patients are evaluated after eradication therapy is a serious concern for both the medical care system and medical economy.